Knowledge, Awareness, and Practice of Dentists in Preventing- Novel Corona Virus (COVID-19) Transmission - A Questionnaire Based Cross-Sectional Survey. - Teja, Kavalipurapu Venkata; Vasundhara, Kaligotla V. Apoorva; gummuluri, sriram (Brazilian Dental Science, 2020)
Background: The global issue that urges the public health emergency is the outbreak of the Novel Corona Virus strain (COVID-19). Dentists being are highly prone to airborne transmission during dental treatment due to aerosols generated by various dental procedures on patients with COVID-19. Taking this fact into consideration, the present survey research was mainly aimed at evaluating the knowledge, attitude, and practice of dentists in preventing the disease transmission of Novel Coronavirus (COVID-19). Material and methods: The present study is prospective research, where the online survey questionnaire was distributed among 300 dentists in Andhra Pradesh and Telangana states in India, who were randomly recruited for the study. The participants were recruited based on the clinical experience ranging from less than five years to more than ten years, who were working in both the private and government sectors. 15 close-ended questions were formulated and validated. The questionnaire consisted of the necessary demographic details of the participants and equally distributed into three sections that contained questions that assessed the knowledge, attitude, and practice of dentists in preventing the disease transmission of Novel Coronavirus (COVID-19). Results: The results revealed that dentists have an adequate knowledge and awareness on COVID-19 transmission and most of the dentists felt that dentists have a major role in preventing the disease transmission. Majority of the participants raised the importance of awareness programs have to be conducted on various measures in preventing COVID-19 transmission among dental fraternity and in public. Conclusions: From the survey research it can be concluded that dentists have an adequate knowledge and awareness on COVID-19 disease. Majority of them are trying their level best in the present situation to prevent COVID-19 transmission. Keywords COVID-19; Dentists; Infection control.